2012
DOI: 10.28927/sr.352201
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the Mechanical Behavior of Fiber Reinforced Sand using the Discrete Element Method

Abstract: The general characteristics of granular soils reinforced with fibres have been reported in previous studies and have shown that fibre inclusion provides an increase in material strength and ductility and that the composite behaviour is governed by fibre content, as well as the mechanical and geometrical properties of the fibre. The present work presents a numerical procedure to incorporate fiber elements into an existing discrete element code (GeoDEM). The fiber elements are represented by linear elastic-plast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The macroscopic material properties of fibre-reinforced soils have been studied in the laboratory by many researchers [ 5 , 6 , 7 , 8 , 9 ]. Additionally, numerical DEM simulations can both quantify these macro-properties as well as the mechanical fibre–soil interactions [ 2 , 10 , 11 , 12 ]. Zornberg [ 13 ], for example, analysed the limit equilibrium of soil using the discrete framework.…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic material properties of fibre-reinforced soils have been studied in the laboratory by many researchers [ 5 , 6 , 7 , 8 , 9 ]. Additionally, numerical DEM simulations can both quantify these macro-properties as well as the mechanical fibre–soil interactions [ 2 , 10 , 11 , 12 ]. Zornberg [ 13 ], for example, analysed the limit equilibrium of soil using the discrete framework.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that mixing sand with fibers can effectively improve the mechanical performance of the latter. The tensile strength of the fibers intersecting the shear failure surface in the sand increases the shear strength of the sand (Consoli et al 2002 ; Velloso et al 2012 ; Sotomayor and Casagrande 2018 ; Louzada et al 2019 ; Ghadr and Bahadori 2019 ; Correia et al 2021 ). Previous studies also showed that the reinforcement type, length, aspect ratio, content, and particle size affect reinforcement effectiveness (Ibraim et al 2010 ; Michalowski and Cermak 2002 ; Ghadr and Bahadori 2019 ; Ghadr 2020 ).…”
Section: Introductionmentioning
confidence: 99%